What Affects Farmers' Ecocompensation Expectations? An Empirical Study of Returning Farmland to Forest in China. (June 2019) - Zhang, Baojian; Li, Pengli; Xu, Yan; Yue, Xiaohang
Ecocompensation projects (EPs) have two primary objectives: environmental protection and the livelihood maintenance of farmers. Farmers' ecocompensation expectations (FEEs) are a key factor that affects whether the design of ecological policy is targeted at practical problems. This article divides FEEs into three dependent variables and uses logistic regression and multiple regression models to analyze the influencing factors of FEEs. The results of a questionnaire survey based on 259 farmers in the area of Returning Farmland to Forest Project, with tropical and subtropical regions of China included, show that, first, farmers' willingness to participate in EPs is strong. Several indicators, such as policy cognition level, returned farmland area, and participation in other EPs, have been demonstrated to significantly affect farmers' willingness to participate. Second, the result of the contingent valuation method shows that farmers' expectations of compensation income are higher than the current standard. Farmers' returned farmland area, participation in other EPs, and degree of satisfaction with the policy effect are primary influencing factors. Third, farmers' expectations of compensation mode, such as employment opportunities, technical guidance, and ecological migration, are greatly improving. The choice of compensation mode is mainly affected by policy cognition level, current compensation mode for returning farmland, and degree of satisfaction with the policy effect. This study can provide a new perspective for the policy adjustment of eco-environmental protection and farmers' livelihood choices in the tropical and subtropical regions of China.